1959
DOI: 10.1152/jappl.1959.14.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical subdivisions of the volume of respiratory dead space and effect of position of the jaw

Abstract: The mean volume of the extrathoracic respiratory tract in six cadavers was found to be 72 ml (BTPS), (S.D. ±32). Expressed as a fraction of body weight in pounds this amounted to 0.55. The intrathoracic anatomical dead space was measured in three intubated subjects. The mean value was 66 ml (BPTS), (S.D. ±29) or 0.43 times the body weight in pounds. The influence of the position of the jaw on the dead space was studied in the six cadavers and three conscious subjects. Depression of the jaw with flexion of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(33 citation statements)
references
References 0 publications
2
31
0
Order By: Relevance
“…5). Nunn, Campbell, and Peckett (21) reported that 72±32 ml (mean±+SD) of the total dead space was outside the thorax. This suggests that the airways which increase in volume with DOPSI are within the thorax.…”
Section: Discussionmentioning
confidence: 99%
“…5). Nunn, Campbell, and Peckett (21) reported that 72±32 ml (mean±+SD) of the total dead space was outside the thorax. This suggests that the airways which increase in volume with DOPSI are within the thorax.…”
Section: Discussionmentioning
confidence: 99%
“…2 In contrast, one study in cadavers determined the anatomic dead space of the extrathoracic airways (not including the trachea and main bronchi) to be ϳ75 mL. 19 With a tidal volume of 400 mL, the 70 mL lost in the upper airway would reduce the inhaled dose by a calculated 17.5%. This rationale seems to agree with our findings of reduced lung dose with the Wright and aerosol masks, which require transit through the upper airway.…”
Section: Role Of Upper Airways In Aerosol Lossmentioning
confidence: 99%
“…This volume has been measured postmortem in adults [66] and whilst dependent to a degree on head position, the volume represents approximately 50% of the anatomical dead space, i.e. 1 mL·kg -1 .…”
Section: Normal Values: Mechanically Assisted Breathingmentioning
confidence: 99%